2019
DOI: 10.2967/jnumed.119.236786
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dosimetry and Biodistribution of 68Ga-FAPI-46 PET Imaging in Cancer Patients

Abstract: Targeting cancer-associated fibroblasts (CAFs) has become an attractive goal for diagnostic imaging and therapy because they can constitute as much as 90% of a tumor mass. The serine protease fibroblast activation protein (FAP) is overexpressed selectively in CAFs, drawing interest in FAP as a stromal target. The quinolinebased FAP inhibitor (FAPI) PET tracer 68 Ga-FAPI-04 has been previously shown to yield high tumor-to-background ratios (TBRs) in patients with various cancers. Recent developments toward an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
121
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(133 citation statements)
references
References 33 publications
12
121
0
Order By: Relevance
“…Data on FAP-specific PET is still limited. While several publications contain at least one patient with breast cancer, no dedicated analysis for target volume delineation has been performed [12,26,32,36,37]. The biggest collective consisted of four patients (3 invasive ductal carcinomas, 1 invasive lobular carcinoma) analyzed by Chen et al who found that FAP-specific PET was able to detect more lymph node metastases than FDG PET in this small sample [25].…”
Section: Breastmentioning
confidence: 99%
“…Data on FAP-specific PET is still limited. While several publications contain at least one patient with breast cancer, no dedicated analysis for target volume delineation has been performed [12,26,32,36,37]. The biggest collective consisted of four patients (3 invasive ductal carcinomas, 1 invasive lobular carcinoma) analyzed by Chen et al who found that FAP-specific PET was able to detect more lymph node metastases than FDG PET in this small sample [25].…”
Section: Breastmentioning
confidence: 99%
“… 1 3 FAP is an overexpression in more than 90% of epithelial carcinomas and some mesenchymal tumors, and recent studies showed that 68 Ga-FAPI might be a broad-spectrum tumor PET agent. 4 6 However, high uptake of 68 Ga-FAPI was also found in nontumorous lesions, including wound healing, inflammation, fibrosis, and so on. 7 , 8 This case again highlighted that 68 Ga-FAPI could gather in nontumorous lesions.…”
mentioning
confidence: 99%
“…Further modifications to the FAPI compounds were performed to improve tumor retention while retaining the imaging contrast obtained with FAPI-02 and FAPI-04 (6,17,31). A further increase of tumor retention time was achieved with FAPI-46 (17,31).…”
Section: Molecular Radiotherapymentioning
confidence: 99%
“…A further increase of tumor retention time was achieved with FAPI-46 (17,31). 68 Ga-FAPI-46 PET/CT imaging had a favorable dosimetry profile and showed high tumor-to-background ratios increasing over time, suggesting more favorable kinetics for potential therapeutic applications (31).…”
Section: Molecular Radiotherapymentioning
confidence: 99%